1998
DOI: 10.1063/1.1149246
|View full text |Cite
|
Sign up to set email alerts
|

Frequency stabilization of a radio frequency excited CO2 laser using the optogalvanic effect

Abstract: Frequency stabilization of a rf excited CO2 laser on the peak of the Doppler broadened gain curve using the optogalvanic effect generated from the laser itself is achieved. The optogalvanic signal is directly coupled from a rf discharge chamber via a capacitor into a detector and a lock-in stabilizer. The frequency stability is estimated to be better then 3×10−8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Upon the first application of lasers in optogalvanic (OG) studies [1], the laser optogalvanic effect found widespread application in various fields [2][3][4][5][6][7][8][9][10][11]. As regards CO 2 lasers, all microscopic laser-plasma processes occurring in such active mediums have been well studied [12][13][14][15], and various OG signal detection methods in DC and RF discharge tubes have been discussed in details [16][17][18][19][20][21]. Moreover, both the dependence of the OG signal phase and amplitude on the laser modulation frequency [22][23][24] and the temporal behavior of signal shapes [25][26][27] have been theoretically and experimentally studied in many previous works.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Upon the first application of lasers in optogalvanic (OG) studies [1], the laser optogalvanic effect found widespread application in various fields [2][3][4][5][6][7][8][9][10][11]. As regards CO 2 lasers, all microscopic laser-plasma processes occurring in such active mediums have been well studied [12][13][14][15], and various OG signal detection methods in DC and RF discharge tubes have been discussed in details [16][17][18][19][20][21]. Moreover, both the dependence of the OG signal phase and amplitude on the laser modulation frequency [22][23][24] and the temporal behavior of signal shapes [25][26][27] have been theoretically and experimentally studied in many previous works.…”
mentioning
confidence: 99%
“…However, DC discharges have always been of interest as a useful alternative due to: 1) simplicity of discharge performance, 2) noncomplexity of the OG signal detection, and 3) a close and direct relationship between OG pulse shapes and temporal variations in irradiated plasma parameters. So, most of the spectroscopic studies requiring well-stabilized plasmas are performed using RF discharges; however, time-dependent investigations on microscopic and quantum properties of the irradiated plasmas are generally done with DC discharges.In the case of RF discharges, the main methods for the OG signal detection include picking up the laser-induced fluctuations in: a) reflected field in a power transmission line [20], b) RF field emitted by a discharge current around a tube [3], and c) plasma transverse current across a couple of transversely positioned electrodes [21]. On the other hand, in DC discharge tubes, the OG signals are always detected by a common sampler capacitor connected to a certain point of the discharge circuit; however, the problem of a risky electric connection of highly sensitive analyzing instruments to high voltages in the discharge circuits is one of the notorious disadvantages of such methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation